Fundamentals of Silicon Carbide Technology : Growth, Characterization, Devices and Applications. - Kimoto, Tsunenobu (Wiley, 2014)
A comprehensive introduction and up-to-date reference to SiC power semiconductor devices covering topics from material properties to applicationsBased on a number of breakthroughs in SiC material science and fabrication technology in the 1980s and 1990s, the first SiC Schottky barrier diodes (SBDs) were released as commercial products in 2001. The SiC SBD market has grown significantly since that time, and SBDs are now used in a variety of power systems, particularly switch-mode power supplies and motor controls. SiC power MOSFETs entered commercial production in 2011, providing rugged, hig.